The C-Type Lectin Receptor SIGNR3 Binds to Fungi Present in Commensal Microbiota and Influences Immune Regulation in Experimental Colitis - Eriksson, Magdalena; Johannssen, Timo; von Smolinski, Dorthe; Gruber, Achim D.; Seeberger, Peter H.; Lepenies, Bernd (Frontiers in Immunology, 2013)
Inflammatory bowel disease is a condition of acute and chronic inflammation of the gut. An important factor contributing to pathogenesis is a dysregulated mucosal immunity against commensal bacteria and fungi. Host pattern-recognition receptors (PRRs) sense commensals in the gut and are involved in maintaining the balance between controlled responses to pathogens and overwhelming innate immune activation. C-type lectin receptors (CLRs) are PRRs recognizing glycan structures on pathogens and self-antigens. Here we examined the role of the murine CLR specific intracellular adhesion molecule-3 grabbing non-integrin homolog-related 3 (SIGNR3) in the recognition of commensals and its involvement in intestinal immunity. SIGNR3 is the closest murine homolog of the human dendritic cell-specific intercellular adhesion molecule-3-grabbing non-integrin (DC-SIGN) receptor recognizing similar carbohydrate ligands such as terminal fucose or high-mannose glycans. We discovered that SIGNR3 recognizes fungi present in the commensal microbiota. To analyze whether this interaction impacts the intestinal immunity against microbiota, the dextran sulfate sodium-induced colitis model was employed. SIGNR3−/− mice exhibited an increased weight loss associated with more severe colitis symptoms compared to wild-type control mice. The increased inflammation in SIGNR3−/− mice was accompanied by a higher level of TNF-α in colon. Our findings demonstrate for the first time that SIGNR3 recognizes intestinal fungi and has an immune regulatory role in colitis.